EXPRESSION AND PURIFICATION OF RECOMBINANT STAPHYLOCOCCAL PROTEIN A FUSED TO A MALTOSE - BINDING PROTEIN - Nurmagambetova , A.B.; Akhmetova , D.G.; Khassenov , B.B.; Baltin , K.K. (Eurasian Journal of Applied Biotechnology, 2017)
Recombinant protein A is widely used in biotechnology for the purification of immunoglobulin G antibodies. In this study, truncated protein A (protein A (5), encoding only five IgG binding domains (E, D, A, B, and C) and lacking signal sequence S and cell-wall anchoring region X M, was cloned into pMBP his parallel 2 and expressed in BL21 (DE3) cells. The gene encoding protein A was inserted downstream of the maltose binding protein (MBP) encoding malE gene. MBP is often fused with other proteins to improve their solubility, enhance stability, and increase the final yield. Proteins expressed using this system can be found in the soluble fraction, which is likely due to the solubilizing properties of MBP. A strain producing recombinant protein A (5) fused with MBP was obtained. The recombinant protein was purified and concentrated by gradient affinity chromatography. The weight of the protein fused with MBP was approximately 77.3 kDa, and without MBP was approximately 37 kDa. The IgG binding specificity of the recombinant protein was assessed using the agar gel immunodiffusion test with the target protein, bull, mouse, rat, and rabbit IgGs. The antigen antibody interaction showed a pattern not character to that described previously.